TEORI PERAN DAN KONSEP EXPECTATION-GAP FUNGSI PENGAWASAN DALAM PENGELOLAAN KEUANGAN DESA - Made Aristia Prayudi; Gusti Ayu Ketut Rencana Sari Dewi; Diota Prameswari Vijaya; Luh Putu Ekawati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
ABSTRACTAlthough the importance of supervisory function on village financial management in Indonesia cannot be debated, there is still some ambiguity in determining what the supervisors actually deliver as well as who the proper party that must do the supervisory. The purpose of this study is to empirically investigate the existence of a supervisory function expectation-gap on Indonesian village financial management. It is also aims at examining the relationship between the extent of supervisory function expected by the Village Consultative Body (Badan Permusyawaratan Desa—BPD) and its performance in supervising village governance. The data was collected through a self-administered questionnaire distributed to the members of BPD, village communities, Camat and the members of regional inspectorate of Buleleng Regency of Bali Province. The results of Mann-Whitney test reveal that there exists a BPD’s supervisory function expectation-gap between the members of BPD and (a) village communities regarding the existed duties and the unreasonable expected duties of BPD; (b) Camat regarding the non-existed duties of BPD; (c) regional inspectorate regarding the existed duties, the non-existed duties and the unreasonable expected duties of BPD. Furthermore, the results of Ordinal Regression analysis indicate a significantly positive relationship between the expectation degree of supervisory function perceived by members of BPD and their performance. The findings have implications for understanding the expectation-gap phenomenon on Indonesian village financial management supervisory and also on the design of capacity building programs initiatives for members of village governance supervisory institutions in Indonesia.